A strategy to increase phosphorescent efficiency without perturbing emission color for benzothiazole-containing iridium phosphors. (October 2017) - Liu, Di; Yao, Ruijuan; Dong, Ruizhi; Jia, Fengju; Fu, Min
Abstract: A series of bis(2-phenylbenzothiozolato- N, C 2′ )iridium(acetylacetonate) derivatives are developed for use in phosphorescent organic light-emitting diodes (PhOLEDs). Fluorine (-F), trifluoromethyl (-CF3 ), N -phenylcarbazole-3-yl (-Cz) and diphenylamino (-Ph2 N) are incorporated at the 5- or 7-site of the benzothiazole ring to adjust the properties and performance of the complexes. The emitting colors of these iridium phosphors are almost independent of the substituents and the substitution positions, but -F or -CF3 always resulted in increased phosphorescence quantum yields and decreased lifetimes in photoluminescence. Furthermore, the 5-F/CF3 -substituted iridium complexes exhibited higher efficiencies than their analogues 7-site isomers in OLEDs. In particular the device based on1 exhibits a maximum luminance efficiency of 64 cd A −1 (21.3%). Theoretical calculations were performed to interpret the negligible color tuning effect. Graphical abstract: Highlights: Novel benzothiazole-containing iridium phosphors were developed by attaching substituents at either 5- or 7-site of the ligands. The emitting color of these phosphors is almost independent of the substituent on these sites. But F or CF3 always resulted in increased phosphorescence quantum yields and decreased lifetimes in photoluminescence. The 5-F/CF3 -substituted iridium complexes exhibited higher efficiencies than their analogues 7-site isomers in their OLEDs. The theoretical study reveals that HOMO/LUMO levels were little affected by the substituents at 5- or 7-site of the ligands.